Carbazole Derivatives’ Binding to c-KIT G-Quadruplex DNA - Agata Głuszyńska; Bernard Juskowiak; Martyna Kuta-Siejkowska; Marcin Hoffmann; Shozeb Haider (Molecules, 2018)
The binding affinities of three carbazole derivatives to the intramolecular G-quadruplex (GQ) DNA formed by the sequence 5′-AGGGAGGGCGCTGGGAGGAGGG-3′, derived from the c-KIT 1 oncogene region, were investigated. All carbazole cationic ligands that differed in the substituents on the nitrogen atom were able to stabilize G-quadruplex, as demonstrated using UV-Vis, fluorescence and CD spectroscopic techniques as well as molecular modeling. The spectrophotometric titration results showed spectral features characteristic of these ligands-bathochromic shifts and initial hypochromicity followed by hyperchromicity at higher GQ concentrations. All free carbazole ligands exhibited modest fluorescent properties, but after binding to the DNA the fluorescence intensity increased significantly. The binding affinities of carbazole ligands to the c-KIT 1 DNA were comparable showing values in the order of 105 M−1. Molecular modeling highlights the differences in interactions between each particular ligand and studied G-quadruplex, which potentially influenced binding strength. Obtained results relevant that all three investigated ligands have stabilization properties on studied G-quadruplex.